Issues in bay’ bithaman al-ajil Islamic home finance (‘BBA’) in abandoned housing projects in Malaysia: an examination of ‘gharar’ - Md Dahlan, Nuarrual Hilal; Shuib, Mohd Sollehudin; Mohd Noor, Fauziah (IISTE, 2017)
Islamic Banking has been established since 1980s in Malaysia.It was initially commenced with the incorporation of Bank Islam Malaysia Berhad (BIMB) in 1983.Until today, Islamic Banking has robustly developed in Malaysia providing various kinds of Islamic transaction products including Islamic Home Finance.Various Islamic Home Finance products have been introduced and practised in Malaysia. Among the products are: Bay’ Bithaman al-Ajil (BBA), Musharakah al-Mutanaqisah (MM), Commodity Murabahah and Ijarah.Nonetheless, there are many issues in these products when faced with the problems of abandoned housing projects. One of the issues is the issue of ‘gharar’ in BBA. It is evident that, the application of BBA is proven to be defective and contains many flaws, if involves abandoned housing projects in Malaysia.This paper aims to highlight and analyse this issue (gharar) and provide solutions to the issues discussed. This paper used shariah (Islamic Law) doctrinal and qualitative case study research methodologies. This paper finds that the current terms in the BBA are inadequate and warranted it to be provided with terms that can prevent the occurrences of gharar thus can fully comply with the requirements of the shariah (lslamic Law).The outcome of this paper will help the Islamic banking industry in dealing with the issues of gharar in abandoned housing projects in Malaysia and protect the rights and interests of the purchaser consumers.